Utilising the urban tree waste as alternative for furniture lumber: a case study in Kuala Lumpur - Alli, Hassan; Hishammuddin, Ummu Aiman; Mohd Tahir, Osman; Mohd Taram, Emran; Sulaiman, Ruhaizin (Universiti Putra Malaysia, 2021)
Most urban trees need a periodic process such as branch pruning to fulfil the requirements of the quintessential characteristics related to its longevity, safety, and removal, based on specific reasons. These processes contribute towards the increment of waste capacity and the cost of maintenance. Therefore, waste should be managed properly since might become a valuable resource for economic benefit. Thus, the study aims to identify the value of urban tree species whereas their waste can be utilised as an alternative for furniture lumber. Seven major roads were selected in Kuala Lumpur, Malaysia as the areas for the case study. Methods such as literature review and tree inventory were performed to gather significant data. The results acknowledged four valuable urban tree species that can be utilised as furniture lumber. These trees are under the big tree category within 10 to 45 m in height with more than 1m diameters of bolewood, which is their waste is suitable for lumber production. The finding also provides good practice in managing the waste of urban trees for economic worth.